Large‐scale molecular phylogeny of metallic wood‐boring beetles (Coleoptera: Buprestoidea) provides new insights into relationships and reveals multiple evolutionary origins of the larval leaf‐mining habit. (27th October 2014) - EVANS, AMANDA M.; MCKENNA, DUANE D.; BELLAMY, CHARLES L.; FARRELL, BRIAN D.
Abstract The family Buprestidae (jewel beetles or metallic wood‐boring beetles), contains nearly 15 000 species in 522 genera. Together with the small family Schizopodidae (seven species, three genera), they form the superfamily Buprestoidea. Adult Buprestoidea feed on flowers or foliage, whereas larvae are mostly internal feeders, boring in roots or stems, or mining the leaves of woody or herbaceous plants. The subfamilial and tribal classification of Buprestoidea remains unsettled, with substantially different schemes proposed by different workers based on morphology. Here we report the first large‐scale molecular phylogenetic study of the superfamily Buprestoidea based on data from four genes for 141 ingroup species. We used these data to reconstruct higher‐level relationships and to assess the current classification and the origins of the larval leaf‐mining habit within Buprestoidea. In our analyses, the monophyly of Buprestoidea was strongly supported, as was the monophyly of Schizopodidae and its placement sister to Buprestidae. Our results are largely consistent with the generally accepted major lineages of buprestoids, including clearly‐defined agrilines, buprestines–chrysochroines and early‐branching julodines–polycestines. In addition to Schizopodidae, three of the six subfamilies were monophyletic in our study: Agrilinae, Julodinae and the monogeneric Galbellinae (Galbella). Polycestinae was monophyletic with the exception of the enigmatic Haplostethini. Chrysochroinae and Buprestinae were not monophyletic, but were recovered together in a large mixed clade along with Galbella. The interrelationships of Chrysochroinae and Buprestinae were not well resolved; however they were clearly polyphyletic, with chrysochroine genera falling into several different well‐supported clades otherwise comprising buprestine genera. All Agrilinae were contained in a single strongly supported clade. Coraebini were dispersed throughout Agrilinae, with strong nodal support for several clades representing subtribes. Neither Agrilini nor Tracheini were monophyletic. The leaf‐mining genus Paratrachys (Paratracheini) was recovered within the Acmaeoderioid clade, consistent with the current classification, and confirming the independent origins of leaf‐mining within Polycestinae and Agrilinae. Additionally, our results strongly suggest that the leaf‐mining agriline tribe Tracheini is polyphyletic, as are several of its constituent subtribes. External root feeding was likely the ancestral larval feeding habit in Buprestoidea. The apparent evolutionary transitions to internal feeding allowed access to a variety of additional plant tissues, including leaves. Interestingly, the several genera of leaf‐mining agrilines do not form a monophyletic group. Many of these genera are diverse and highly specialized, possibly indicating adaptive radiations.